2013
DOI: 10.1016/j.freeradbiomed.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Administration of the Nrf2–ARE activators sulforaphane and carnosic acid attenuates 4-hydroxy-2-nonenal-induced mitochondrial dysfunction ex vivo

Abstract: The transcription factor NF-E2-related factor 2 (Nrf2) mediates transcription of antioxidant/cytoprotective genes by binding to the antioxidant response element (ARE) within DNA. Upregulation of these genes constitutes a pleiotropic cytoprotective-defense pathway which has been shown to produce neuroprotection in numerous models by decreasing lipid peroxidation (LP) as measured by the neurotoxic LP by-product 4-hyrdoxynonenal (4-HNE). As neuronal mitochondria have previously been shown to be susceptible to ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 49 publications
(65 reference statements)
3
47
0
Order By: Relevance
“…30) In the present study, the synchronous decreases or increases of mitochondrial antioxidative enzymes by D-Gal treatment or UC-MSCs supplementation underlined the involvement of Nrf2/HO-1. Indeed, the Western-blot results demonstrated that the Nrf2/HO-1 activity was inhibited in D-Gal models, on which UC-MSCs treatment showed effective protection on Nrf2/HO-1, suggesting that Nrf2/HO-1 pathway was one target of UC-MSCs in the mitochondrial protective process.…”
Section: Discussionsupporting
confidence: 63%
“…30) In the present study, the synchronous decreases or increases of mitochondrial antioxidative enzymes by D-Gal treatment or UC-MSCs supplementation underlined the involvement of Nrf2/HO-1. Indeed, the Western-blot results demonstrated that the Nrf2/HO-1 activity was inhibited in D-Gal models, on which UC-MSCs treatment showed effective protection on Nrf2/HO-1, suggesting that Nrf2/HO-1 pathway was one target of UC-MSCs in the mitochondrial protective process.…”
Section: Discussionsupporting
confidence: 63%
“…27 Specifically, SFN-induced activation of ARE has been shown to prevent cell death from oxidative insults and glutamate toxicity in neuronal cells, from photooxidative damage 28 and oxidative stress 29 in retinal pigment epithelial cells, and from electrophilic stress in rat aortic, smooth muscle cells. 30 Moreover, animal models have been developed to evaluate Nrf2-ARE cytoprotection, [31][32][33] and numerous clinical studies have utilized SFN for treatment of prostate cancer, cystic fibrosis, cardiovascular disease, and asthma, among many others (ClinicalTrials.gov). [19][20][21] Thus, there is considerable evidence supporting the notion that activation of the Nrf2 pathway could be a useful therapeutic target for treating chronic degenerative conditions such as FECD.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism by which melatonin increases Nrf2 expression is related to the dissociation of Nrf2/ Keap 1 (repressor) and translocation of Nrf2 to the nucleus, where it binds to the ARE in the promoters of the genes involved in antioxidant protection such as SOD, catalase, GxP and HO-1 (Jaiswal 2004;Osburn et al 2006). It has been reported that Nrf2 activators protect from oxidative injury (Chan et al 2001;Farombi et al 2008;Miller et al 2013). We suggest that melatonin can ameliorate burn-induced liver injury through inhibition of free-radical activating lipid peroxidation, and via the elevation of expression of the transcription factor Nrf2 and antioxidant enzymes such as HO-1.…”
Section: Discussionmentioning
confidence: 99%